Effect of stress on hypertension among professional groups at Bareilly: a cross sectional study - Gupta, Shailesh; Gupta, Shruti (International Journal Of Community Medicine And Public Health, 2019)
Background: The objective of the present study was to study the effect of stress on hypertension in various professional groups. Methods: A cross sectional study was done from 1st August 2015 to 30th August 2017 in district Bareilly. A predesigned and pretested questionnaire was used comprising of demographic data and stress. Three types of professionals were included in this study: doctors, managerial staff and school teachers from the teaching institutions. Results: This study showed association of hypertension with stress level and found that 24.62% doctors, 72.31% school teachers and 27.69% managerial staff were hypertensive with mild stress level. Among all study subjects 41.54% were hypertensive with mild stress level. 15.38% doctors, 10.77% school teachers and 46.92% managerial staff were hypertensive with moderate stress level. Among all study subjects 24.36% were hypertensive with moderate stress level. 46.15% doctors, 0.76% school teachers and 8.46% managerial staff were hypertensive with severe stress level. Among all study subjects 18.46% were hypertensive with severe stress level. Chi-square test for association was applied and p-value was found significant for doctors, managerial staff and insignificant in school teachers. Among all study subjects p value 0.016 was found significant. Conclusions: The present study showed highly significant association for hypertension with stress level among doctors and managerial staff with p value (0.005) and (0.001).